THE ANALYSIS OF FACTORS THAT INFLUENCE COMPANIES’ VALUES - Acep Suherman; Elan Eriswanto (University Muhammadiyah Aceh, 2020)
The research was aimed at analyzing the factors that influenced company’s value that consisted of assets, equity and profit. The research method applied was associative with quantitative approach; the population researched was amounted to 24 companies by using financial statements in the periods of 2019, 2018 and 2017 with criteria samples. The techniques of analyzing data applied consisted of classic assumption test, hypothesis test, regression test, t test, f test and determination coefficients. The result of the research shows that the companies’ condition observed from the aspects of assets growth, equity, profit and stock price are stated to undergo increment. The biggest growth is from the aspect of assets. The result of hypothesis test shows that all independent variables that consist in assets growth, equity, profit and stock price do not have significant influence toward companies’ value